A prospective study on the impact of gestational diabetes mellitus on auditory function in newborn - C., Sravani Chithra; C., Saranya Chithra; Karnal C., Suhashini; Kumari S., Sampath; S., Vidhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Gestational diabetes is a potential risk factor for neonatal hearing loss. Increased circulating sugars in mothers during pregnancy can impair the micro circulation and can cause congenital anomalies of the inner ear resulting in congenital hearing loss. Prevalence of deafness in neonates of mothers with diabetes mellitus is 4.16%. Otoacoustic emissions (OAE) and brainstem evoked response audiometry (BERA), are used to evaluate hearing impairment. Methods: This prospective case-control study was conducted by the Department of Obstetrics and Gynecology, among 92 antenatal mothers between the age of 21 to 35 years, who were classified into two groups, based on their gestational diabetes status. All these newborns were screened for hearing as per universal protocol using OAE within 72 hours of birth and on the 10th day. The aim of the study is to ascertain the effects of gestational diabetes mellitus on auditory function in newborns. Results: In this study a total of 92 pregnant women were selected and divided into two groups, A and B. The mean age was observed as 27.8±5.4 year. On assessment done within 72 hours after birth, 39.1% (18) of the neonates in group A failed in OAE, whereas only 8.7% (4) of the neonates in group B failed in OAE. Children born to mother with gestational diabetes mellitus are at a 6.7 times higher risk to develop congenital hearing loss. Conclusions: This present study shows a significant association between gestational diabetes mellitus and neonatal hearing impairment. Neonates born to GDM mothers had higher failure rate in OAE screening compared to neonates born to non-GDM mothers.